Linking soil moisture status of winter sports pitches to measures of playing quality - Jennings-Temple, Marke (Cranfield University, 2005)
A review of traction and hardness Performance Quality Standard tests highlighted significant relationships with soil and grass factors. Inadequate guidance to achieve test results through pitch management means that management practices can not focus on injury prevention or playing quality. A clear link between factors that can be managed by Groundsmen and the traction and hardness tests is required. The concept of effective stress significantly linked moisture status to soil strength in the laboratory. Penetration resistance was shown to be complex and affected by grass roots and bulk density, which prevented a single model encompassing all soil types to be established. Prediction of traction and hardness used grass and soil factors and varied according to soil type and wet or dry test conditions. In situ tests showed no variation due to pitch test position and as sand content increased, prediction became less reliable. A decision support model used the regression results to provide Groundsmen with the ability to monitor pitch quality in real-time. Effective stress successfully linked moisture status and strength although in situ verification is required. Regression analysis and the decision support model will assist Groundsmen in managing pitches while targeting playing quality. Further research to understand how management practices impact on quality and to understand the link between injury rates and type, and the results of traction and hardness tests is required. This knowledge will enable a company to simultaneously differentiate itself from competition and create a barrier to potential entrants.